Multidimensional Poverty Index 2011 : two page briefing - Oxford Poverty & Human Development Initiative (OPHI) (Oxford Poverty & Human Development Initiative (OPHI), 2011)
The Multidimensional Poverty Index (MPI) is an international measure of poverty. Covering 109 developing countries, the MPI complements income poverty and Millennium Development Goals (MDGs) measures by reflecting the acute deprivations that people face at the same time. It identifies people who contend with multiple deprivations across three dimensions: education, health, and living standards. The MPI was developed by the Oxford Poverty and Human Development Initiative (OPHI) and the United Nations Development Programme Human Development Report Office (UNDP HDRO) for the UNDP’s flagship Human Development Report.